Effects of temperature and salinity on the decapsulation of Artemia cyst (Bangladesh Journal of Zoology, 2018)
A study was performed to determine to effect of salinities (20, 25, 28, 30, 32, 35 and 40 ppt) and temperatures (20, 24, 28, 30 and 32°C) on the decapsulation of Artemia cyst. The dry Artemia cyst were hydrated up to 2 hrs in fresh water at (26 ± 1ºC) temperature with a density 0.3 g/ 50 ml water. Saline water was prepared using salt (NaCl) and hatching rate of Artemia cyst was counted after 36 hours of incubation. Highest hatching rate (72.59 ± 5.03), (75.84 ± 3.67), (74.45 ± 0.83), (89.38 ± 0.96), (76.46 ± 4.63), (70.58 ± 9.51) and (69.17 ± 0.70)% were observed in 20, 25, 28, 30, 32, 35 and 40 ppt salinities at 32, 28, 28, 24, 24, 24, and 28°C temperature, respectively. Lowest hatching rate (57.03 ± 3.67), (47.97 ± 8.06), (46.20 ± 8.17), (39.58 ± 10.12), (47.36 ± 7.04) (25.86 ± 8.10) and (20.57 ± 2.71) % were measured in 20, 25, 28, 30, 32, 35 and 40 ppt salinities at 30, 32, 32, 32, 32, 32 and 32°C, respectively. The maximum hatching rate (89.38 ± 0.96)% was found in 30 ppt salinity at 24°C temperature and minimum hatching rate (20.57 ± 2.71) % was observed in 40 ppt salinity at 32°C temperature. Therefore, 30 ppt salinity and 24οC temperature could be the optimum salinity-temperature for Artemia cyst decapsulation.Bangladesh J. Zool. 46(2): 197-204, 2018